2018
DOI: 10.1002/sdtp.12154
|View full text |Cite
|
Sign up to set email alerts
|

P‐31: A Statistical Paradigm for Assessment of Subjective Image Quality Results

Abstract: ISO/IEC 29170-2 outlines a subjective procedure for assessing codec quality for near-threshold artifacts. Here we outline a statistical method for analyzing these data using Generalized Linear Mixed-Models (GLMMs). This procedure provides insightful metrics concerning the relative performance of two or more codecs that may aid in the perceptually-guided development and selection of novel codec technologies.Author Keywords subjective quality assessment; image compression; statistical modeling P-31 / M. D. Cuton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The rationale for bypassing the color conversion was that it would improve the compression performance and produce fewer visible artefacts. To assess this hypothesis, the VDC-M and DSC data were separately fitted using a Generalized Linear Mixed Model (GLMM) (11) (12). The analysis showed that there was no overall effect of bypassing color conversion for either codec.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for bypassing the color conversion was that it would improve the compression performance and produce fewer visible artefacts. To assess this hypothesis, the VDC-M and DSC data were separately fitted using a Generalized Linear Mixed Model (GLMM) (11) (12). The analysis showed that there was no overall effect of bypassing color conversion for either codec.…”
Section: Resultsmentioning
confidence: 99%
“…To test the two hypotheses, the flicker paradigm data was fitted using a Generalized Linear Mixed Model (GLMM) 32 following the approach described by Cutone et al 33 for the analysis of 2D image quality assessment data. GLMM analysis was performed using the R statistical software environment (R Core Team 2017) and maximum likelihood estimation was used for fitting data using lme4's “glmer.” Before fitting GLMM, control data were excluded because these are unrelated to the experimental hypotheses and including control data can cause convergence failure as the correct response proportions were typically 1.0 for control data.…”
Section: Resultsmentioning
confidence: 99%